2007
DOI: 10.1124/jpet.107.127019
|View full text |Cite
|
Sign up to set email alerts
|

μ-Opioid Receptor Up-Regulation and Functional Supersensitivity Are Independent of Antagonist Efficacy

Abstract: Chronic opioid antagonist treatment up-regulates opioid receptors and produces functional supersensitivity. Although opioid antagonists vary from neutral to inverse, the role of antagonist efficacy in mediating the chronic effects of opioid antagonists is not known. In this study, the effects of two putative inverse agonists (naltrexone, naloxone) and a putative neutral antagonist (6␤-naltrexol) were examined. Initially, peak effect (40 min, naltrexone and naloxone; 70 min, 6␤-naltrexol) and relative potency t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 38 publications
7
21
0
Order By: Relevance
“…In the case of naltrexone, after opioid detoxification or if a scheduled dose is missed, patients have reduced tolerance to opioids and are vulnerable to overdose. Although opioid antagonists up‐regulated μ‐receptors and induced supersensitivity to morphine in a mouse model,91 healthy humans show no evidence of μ‐receptor up‐regulation in the respiratory control system, the most likely site of opioid overdose lethality 92. Overall, the risk of overdose is significantly lower in patients who are actively involved in medication‐assisted treatment whether it is with methadone, buprenorphine, or naltrexone 93.…”
Section: Current Approach To Treatment Of Opioid Use Disorder: Choosimentioning
confidence: 95%
“…In the case of naltrexone, after opioid detoxification or if a scheduled dose is missed, patients have reduced tolerance to opioids and are vulnerable to overdose. Although opioid antagonists up‐regulated μ‐receptors and induced supersensitivity to morphine in a mouse model,91 healthy humans show no evidence of μ‐receptor up‐regulation in the respiratory control system, the most likely site of opioid overdose lethality 92. Overall, the risk of overdose is significantly lower in patients who are actively involved in medication‐assisted treatment whether it is with methadone, buprenorphine, or naltrexone 93.…”
Section: Current Approach To Treatment Of Opioid Use Disorder: Choosimentioning
confidence: 95%
“…Studies strongly suggest that the commonly used opioid antagonists naloxone and naltrexone display negative efficacy and are therefore classified as inverse agonists (Costa and Herz, 1989;Wang et al, 2001;Marczak et al, 2007). Although all opioid antagonists are capable of reversing or blocking the effects of opioid agonists, only inverse agonists inhibit signaling of constitutively active opioid receptors (Wang et al, 2004;Sadée et al, 2005;Sirohi et al, 2007). However, in the absence of constitutive receptor activity, inverse agonists are generally indistinguishable from neutral antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…The ED 50 value to block fentanyl subcutaneously induced analgesia (100 g/kg) was estimated for subcutaneous naltrexone, naloxone, and 6␤-naltrexol. The peak effect for all antagonists was determined previously (Sirohi et al, 2007;(naltrexone and naloxone, 40 min;6␤-naltrexol, 70 min). Next, the dose-response function and LD 50 value for fentanyl were determined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that continuous administration of nonselective opioid antagonists, such as naloxone and naltrexone, will up-regulate the number of receptors and increase the potency of -and -opioid agonists (Morris et al, 1988;Paronis and Holtzman, 1991;Sirohi et al, 2007). Similar increases in potency of a -agonist might be expected during chronic treatment with buprenorphine on the basis of its -antagonist actions; the present results provide no evidence of sensitization to the behavioral effects of U50,488 during daily treatment with 0.32 mg/kg buprenorphine.…”
Section: Discussionmentioning
confidence: 99%